2022
DOI: 10.1002/mde.3737
|View full text |Cite
|
Sign up to set email alerts
|

Online retailers' price structure decisions in competitive markets: A structure–conduct–performance framework

Abstract: It is theoretical and managerial significant to explore the determinants of retailers' decisions between a combined price structure and a partitioned price structure and the effect of their decisions on a manufacturer's product sales in competitive markets. Based on the structure–conduct–performance framework, we reveal that market structure‐related characteristics, such as the number of retailers, the degree of retailer differentiation, whether a dominant retailer in the market, and the number of product subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 101 publications
(196 reference statements)
0
3
0
Order By: Relevance
“…Our research is also closely related to the examination of power structure and its impact on corporate decision-making and performance (Chai et al, 2021;Luo et al, 2017;Wang et al, 2023). Numerous studies focus on the game between supply chain members under various supply chain power structures (Lu & Menezes, 2024;Zhang et al, 2022).…”
Section: Power Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Our research is also closely related to the examination of power structure and its impact on corporate decision-making and performance (Chai et al, 2021;Luo et al, 2017;Wang et al, 2023). Numerous studies focus on the game between supply chain members under various supply chain power structures (Lu & Menezes, 2024;Zhang et al, 2022).…”
Section: Power Structurementioning
confidence: 99%
“…In the competitive landscape, market leaders typically possess greater financial resources and market influence, enabling them to exploit these assets to access abundant information and acquire a privileged decision-making position (Luo et al, 2017;Wang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that merely changing the format or frame of the prosocial campaign information can alter people's thoughts, attitudes, and eventually behavior. For instance, previous studies have shown that message appeals presented in positive and negative frames (e.g., Grewal et al, 1994;Kim and Song, 2023), framing of attribute information of a product (e.g., 75% lean vs. 25% fat) (e.g., Levin and Gaeth, 1988), framing of gain and loss (e.g., Nabi et al, 2020;Gantiva et al, 2021;Gursoy et al, 2022;Kim, 2022;Peng et al, 2022;Stadlthanner et al, 2022;Ort et al, 2023), and presentation of prices (e.g., partitioned price vs. all-inclusive) (e.g., Morwitz et al, 1998;Hamilton and Srivastava, 2008;Völckner et al, 2012;Choi et al, 2020;Marquez et al, 2022;Wang et al, 2023) can yield different results depending on the way the information is presented.…”
Section: Introductionmentioning
confidence: 99%